Risk Management Analysis of Organic and Inorganic Rice Farming in Serdang Bedagai Regency - Savira, Nadila; Ayu, Sri Fajar; Iskandarini, Iskandarini (Westscience Press, 2025)
Farming risk management is a step that can affect the production results of the farming. This study aims to analyze the strategies used by farmers in managing risks in the field. The analysis method used is Coevisian variation to see the level of risk of farming, measuring perception using a likert scale and using 3 strategy management, namely Ex-ante, interactive and Ex-post. The results of this study show that the level of risk of farming is low and the perception is positive.